1996
DOI: 10.1108/09604529610149211
|View full text |Cite
|
Sign up to set email alerts
|

Effective performance management ‐ the teamwork approach considered

Abstract: Effective performance management -the teamwork approach considered Hadyn Ingram Brenda McDonnell Article information:To cite this document:If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The variables that have been identified as most important have been considered by various organization in order to have effective management of human resource (Ingram and McDonnell 1996). Looy et al (2003) have identified collaboration among the employee as important variables to achieve the goals for the organization.…”
Section: The Family and Quality Information Assessmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…The variables that have been identified as most important have been considered by various organization in order to have effective management of human resource (Ingram and McDonnell 1996). Looy et al (2003) have identified collaboration among the employee as important variables to achieve the goals for the organization.…”
Section: The Family and Quality Information Assessmentsmentioning
confidence: 98%
“…To improve productivity of service and production is the objective of layout variable. The ergonomic of work stations, machines and tools that contribute to work flows could influence team work on productivity of organization (Ingram and McDonnell 1996;Ingram 1997). In addition, defining production capacity to match the market demand could contribute to allocation of organizational resources efficiently (McAdam et al 2005).…”
Section: Step Ii: Defining Dimension On Quality For Organizationmentioning
confidence: 99%
“…All these scored relatively low scores ranging between 47% and 67% and therefore need to be addressed to have a near perfect or a perfect PAS. The need to have an effective Performance Appraisal System is supported by Ingram and McDonnell (1996) ;Mullins, (2002) and Verbeeten, (2008) who says that measuring the performance of employees is a compulsory task as it allows a firm to have a record of current firm activity in order to judge their progress and help refocus strategy. This information must always be compared against past performance and initial goals, as well as firms must also compare their performance with other compatible firms.…”
Section: The Linkage Between Performance Appraisal and Firm Performancementioning
confidence: 99%
“…Customers hold service expectations based on many principles, such as experiences, recommendations, publicity, testimonials in which most of the customers compare the perceived service that they have encountered with the expected service before they patronizing any. Ingram and McDonnell (1996) state that service quality is a core element to be focused in service industry as it has become the most highlighted point in any business engagement based on its effect towards customer satisfaction, customer feedback and customer response.…”
Section: Introductionmentioning
confidence: 99%